2008
DOI: 10.3155/1047-3289.58.7.902
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Impacts of Distributed Energy Resources Implemented in the Northeastern United States

Abstract: Emissions from the potential installation of distributed energy resources (DER) in the place of current utility-scale power generators have been introduced into an emissions inventory of the northeastern United States. A methodology for predicting future market penetration of DER that considers economics and emission factors was used to estimate the most likely implementation of DER. The methodology results in spatially and temporally resolved emission profiles of criteria pollutants that are subsequently intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The impacts of DG in the SJV complement the findings in previous studies on DG in other areas in the United States, in southern California (Rodriguez et al 48 ) and northeastern United States (Carreras-Sospedra et al 4 ). Several scenarios of adoption of DG power in the SJV for the year 2023 are developed by varying aggregate DG power, emission specifications of DG technologies, and level of avoided emissions due to the combined heating and power applications of DG power.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The impacts of DG in the SJV complement the findings in previous studies on DG in other areas in the United States, in southern California (Rodriguez et al 48 ) and northeastern United States (Carreras-Sospedra et al 4 ). Several scenarios of adoption of DG power in the SJV for the year 2023 are developed by varying aggregate DG power, emission specifications of DG technologies, and level of avoided emissions due to the combined heating and power applications of DG power.…”
Section: Discussionsupporting
confidence: 81%
“…This study concluded that deployment of DG technologies to meet 10% of increased power demand leads to ozone increases on the order of 1 ppb and PM by 1 mg/m 3 . More recently, Carreras-Sospedra et al 4 applied the Community Multiscale Air Quality (CMAQ) model to study air quality effects of DG deployment to replace highly polluting central plants in northeastern United States and concluded that significant air quality benefits can be realized through DG.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Depending on the magnitude, location and type of DG, they found decreases and increases in ambient concentrations of O 3 and PM 2.5 [9]. Carreras-Sospedra et al ran similar scenarios in the Northeast United States, but retired older base-load generation such as pulverized coal plants [10]. By contrast to Rodriguez et al [9], O 3 and PM 2.5 decreased in these scenarios.…”
Section: Introductionmentioning
confidence: 92%
“…Park et al [47] continued consideration of the use of electron beam technology (EB) used to simultaneously remove SO 2 and NO x from the combustion components of flue gases emitted from a power plant. Emissions primarily depend on the type of fuel burned at power plants: solid fuel leads to a high concentration of emissions [41,48,60], another type of power plant fuel is natural gas, the emissions effects of which were investigated by [10,23,46] compared different emission generation scenarios (point and mobile sources) from a power plant, using a 3D microscale model of chemical transport, as the distribution of pollutants studied in the mesome scale models does not allow to solve high gradients of air pollution. The use of parameterized microscale models such as OSPM [6], SIRANE [57] or ADMS-URBAN [52] is widely used for air quality modeling.…”
Section: Introductionmentioning
confidence: 99%